Consolidation of the Russian society under contemporary challenges: Social-historical and value contexts - M. K. Gorshkov; I. O. Tyurina (RUDN journal of Sociology, 2023)
Civil identity is one of the key resources for uniting Russian society. It is based on the historical self-awareness, common historical memory, joint commemoration of significant historical events and achievements of the state and society. Civil identity of the Russian nation is concentrated around the Soviet legacy: Russian reality is filled with Soviet reminiscences and markers of historical memory, many of which act as ‘links’ for the differentiated social space. However, the Soviet period is becoming increasingly distant, full of myths and simplified interpretations. Therefore, the increased attention to the interpretation of ambiguous events of the Soviet history may cause a critical revision of the Soviet value paradigm in relation to the historical heritage and the policy of memory and become a catalyst for centrifugal sentiments, creating threats to the state security and integrity. The efficiency of state institutions and prospects of civil society structures depend on the dominant identity markers in the mass consciousness and on the most important reference groups for self-identification. Thus, the study of the historical consciousness and memory of Russians as the basic principles of national consensus and the analysis of the features of the post-crisis historical worldview of different groups in the Russian society are of particular relevance. Based on the monitoring research data from the IS FCTAS RAS surveys (conducted in 2020-2023 on the representative all-Russian regionalized quota sample; N = 2000) and an integrated approach, the authors assess the historical and value consciousness of Russians under contemporary challenges: interest in history and historical facts, perception of historical periods and leading historical figures; attitude to national history, formation of the all-Russian identity and the role of family memory in this process; a ‘new vision’ of Russia and its future, a trend to rethink the idea of change and the path of national development, understood in the mass consciousness through the original model of the world order and civilizational sovereignty; ideas about key social groups that contribute to or hinder national development, and about the tasks to be solved on the path to creating future Russia. The main conclusions of the research are presented in the article in the form of postulates.